Third-generation CD19.CAR-T cell-containing combination therapy in Scl70+ systemic sclerosis - Merkt, Wolfgang; Freitag, Merle; Claus, Maren; Kolb, Philipp Leonhard; Falcone, Valeria; Röhrich, Manuel; Rodon, Lea; Deicher, Franca; Andreeva, Ivana; Tretter, Theresa; Tykocinski, Lars-Oliver; Blank, Norbert; et al. (Annals of the rheumatic diseases, 2024)
No effective treatment of systemic sclerosis-associated interstitial lung disease (SSc-ILD) exists. Numerous evidences support the importance of adaptive immunity in SSc-ILD. A basket trial showed higher efficacy of mycophenolate when combined with rituximab in non-specific interstitial pneumonia (NSIP), the most frequent pattern in SSc-ILD.1 Deep B-cell depletion outperforms rituximab in connective tissue diseases,2 3 prompting us to combine these principles in SSc-ILD. - - We here report on a 38-year-old woman suffering from Scl70+SSc with rapid progressive NSIP in which we added CD19.CAR-T-cells to a pre-existing therapy with mycophenolate/nintedanib (figure 1A). Stably elevated highly sensitive troponin T (hsTNT) levels were interpreted as mild myocardial involvement, pulmonary arterial hypertension was excluded. Except for mild obesity and a long-ago history of smoking, the medical history was empty. The disease progressed despite cyclophosphamide, mycophenolate and nintedanib. The latter was initiated because the criteria for progressive pulmonary fibrosis (PPF) were met.4 - - - - Figure 1 - Multimodal therapy including third-generation CD19.CAR-T-cells in a patient with Scl70+systemic sclerosis and progressive pulmonary fibrosis. (A) Graphical overview of disease course and therapeutic regimen. (B) Top: CAR-T-cells rapidly expanded in vivo and were still detectable after 11 months. The graph shows copy numbers of the CAR construct related to the amount of DNA in peripheral blood mononuclear cells (PBMCs), as determined by PCR. Bottom: High-dimensional spectral flow cytometry was used to phenotype persisting CAR-T-cells at months 3 and 7 after infusion. An antibody against the CD19-CAR construct was used to identify CAR-T-cells. Data from the two time points were in silico concatenated and shown together in single graphs. The dot plots show overlays of persisting CAR-T-cells (blue) with non-CAR total (left) and CD8+ (right) T cells after gating on non-doublet, viable, CD45+CD3+ lymphocytes. (C) B-cell counts were determined by standard conventional flow cytometry. No B-cells could be detected after CAR-T therapy. In …